2020
DOI: 10.1055/s-0040-1707141
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Electrochemical Synthesis through Automated Flow: Efficient Synthesis of Chalcogenophosphites

Abstract: Integrated electrochemical reactors in automated flow systems have been utilised for chalcogenophosphite formations. Multiple electrochemical reactions can be performed using a programmed sequence in a fully autonomous way. Differently functionalised chalcogenophosphites have been efficiently synthesised in short reaction times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Based on the experimental observation and literature precedents, a plausible mechanism for this electrochemical fluorination of P­(O)–H motifs is proposed in Scheme . Initially, Cl – was electrooxidized to Cl • , followed by hydrogen atom abstraction (HAT), and phosphorus radical intermediate I was formed.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Based on the experimental observation and literature precedents, a plausible mechanism for this electrochemical fluorination of P­(O)–H motifs is proposed in Scheme . Initially, Cl – was electrooxidized to Cl • , followed by hydrogen atom abstraction (HAT), and phosphorus radical intermediate I was formed.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This review demonstrated the efficacy of the electrosynthesis as an excellent, efficient and green way for constructing new bond such as CÀ P, OÀ P, NÀ P, SÀ P, and SeÀ P. Even with this progress, still the need to develop the catalyst-free bond process, especially for NÀ P and OÀ P bonds. Additionally, there has been made recent progress to access phosphorylated compounds using flow and automated technology [57] that would be an additional step for easy handling of chemicals and less involvement of human, allowing the chemists, at the same time, to apply their expertise to other pressing challenges in their fields.…”
Section: Discussionmentioning
confidence: 99%
“…In the same year, the group of Wirth [57] demonstrated that automated flow electrochemical reactor was successfully useful for the synthesis of organoselenophosphorus (scheme 39). With diphenyl diselenide and phosphites derivatives a large scope of desired compounds was formed in moderate to good yields.…”
Section: Sà P Bond Formationmentioning
confidence: 99%
“…Much effort has been committed to exploring synthetic methods for the construction of P–Se/P–S bonds over the past few decades. The existing methods for constructing P–Se/P–S bonds are often related to transition metal catalysis, strong oxidants, base catalysis, photocatalysis, electrochemical methods, etc. ,, However, some of the existing methods have the disadvantages of being a multistep reaction, using toxic reagents, requiring harsh reaction conditions, requiring long reaction times, having low functional group tolerance, etc. For example, in 2016, an efficient Pd catalyst dehydrogenative coupling method for constructing a P–S bond with good yields was reported .…”
Section: Introductionmentioning
confidence: 99%